Study about the technique of determining residual stress of loading measuring method - Hong, Liu; Zheqi, Jiang; Danqi, Pan (Advances in mechanical engineering, 2021)
Nondestructive test method for residual stress in a structural member is always an important research subject, as a new technique for measuring residual stress loading measuring method needs to consummate for the convenience of engineering. The paper proves that nondestructive test loading measuring method is effective and accurate when compared with the result from hole-drilling method. Taking the measurement of residual stress of injection-molded part in automotive lamp as example, the residual stresses in the surface of injection-molded parts of automotive lamp measured by the two methods are very close based on the two measuring results. It shows that loading measuring method, a new method is used to measure the residual stress, has enough accuracy and credibility when it is used to measure the residual stress of complicated injection-molded part. It provides a basis for popularization and application of loading measuring method in engineering. The paper discusses the basic principles of loading measuring method and detailed procedure of the measurement of residual stress by loading measuring method; it gives out some advices to reduce the test errors.